Religious terms of Persian origin in the Kazakh language. - Zhiyekbaeva. А. B.; Boranbayeva., A. Zh. (Journal of Oriental Studies, 2016)
The article also considers some of religious terms which were borrowed from Farsi and still being used in the modern Kazakh language and Kazakh people’s everyday life. There have been made comparative work on definitions of these religious terms.